Quantity surveyors’ perception of construction health & saftey regulation in Nigeria - Famakin, Ibukun Oluwadara; Fawehinmi, Olaotan Steve (Penerbit UKM, 2012)
The construction industry business in Nigeria like in other countries cannot be tackled effectively without harnessing the construction health and safety regulations to safeguard the health of the workers and the entire community. This paper seeks to assess quantity surveyors’ perception of construction health and safety regulations in Nigeria. Data was collected using the questionnaire survey distributed among Nigerian quantity surveyors and statistical tools employed include percentages and mean score ranking. The study revealed that construction health and safety is still perceived to be more important than the traditional project parameters in the form of cost and quality. Improved quality is discovered to have the greatest impact of construction health and safety on project parameter. The study recommends that health and safety should be included as a project parameter and that related practice notes and guidelines should be evolved for all project stakeholders.